Assessment of ambient dust pollution status at selected point sources (residential and commercial) of Mingaladon area, Yangon region, Myanmar. Issue 1 (15th January 2018) - Tun, Sai Nyan Lin; Aung, Than Htut; Mon, Aye Sandar; Kyaw, Pyay Hein; Siriwong, Wattasit; Robson, Mark; Htut, Than
Abstract : Purpose: Dust (particulate matters) is very dangerous to our health as it is not visible with our naked eyes. Emissions of dust concentrations in the natural environment can occur mainly by road traffic, constructions and dust generating working environments. The purpose of this paper is to assess the ambient dust pollution status and to find out the association between PM concentrations and other determinant factors such as wind speed, ambient temperature, relative humidity and traffic congestion. Design/methodology/approach: A cross-sectional study was conducted for two consecutive months (June and July, 2016) at a residential site (Defence Services Liver Hospital, Mingaladon) and a commercial site (Htouk-kyant Junction, Mingaladon) based on WHO Air Quality Reference Guideline Value (24-hour average). Hourly monitoring of PM2.5 and PM10 concentration and determinant factors such as traffic congestion, wind speed, ambient temperature and relative humidity for 24 hours a day was performed in both study sites. CW-HAT200 handheld particulate matters monitoring device was used to assess PM concentrations, temperature and humidity while traffic congestion was monitored by CCTV cameras. Findings: The baseline PM2.5 and PM10 concentrations of Mingaladon area were (28.50±11.49) µ g/m 3 and (52.69±23.53) µ g/m 3, means 61.48 percent of PM2.5 concentration and 54.92 percent of PM10 concentration exceeded than the WHO reference value during the study period. PM concentration usually reached a peak during early morning (within 3:00 a.m.-5:00 a.m.) and at night (after 9:00 p.m.). PM2.5 concentration mainly depends on traffic congestion and temperature (adjusted R 2 =0.286), while PM10 concentration depends on traffic congestion and relative humidity (adjusted R 2 =0.292). Wind speed played a negative role in both PM2.5 and PM10 concentration with r =−0.228 and r =−0.266. Originality/value: The air quality of the study area did not reach the satisfiable condition. The main cause of increased dust pollution in the whole study area was high traffic congestion ( R 2 =0.63 and 0.60 for PM2.5 and PM10 concentration).